Pol α-primase dependent nuclear localization of the mammalian CST complex - Joseph M. Kelich (Nature Portfolio, 2021)
Kelich, Papaioannou and Skordalakes investigate the intracellular localization dynamics of the mammalian CST, a protein complex critical for telomere maintenance and homeostasis. They find that the CST complex localizes to the nucleus in a cell cycle-dependent manner that requires binding by Pol α-primase and that mutations affecting its nuclear import are associated with human telomere syndromes and cancer.